Improving security, preserving privacy. - Cass, S. (IEEE spectrum)
Although terrorism is probably the focus of most people's current concern, the need for protection from such nightmares as workplace and school violence has been fanning a demand for more secure environments for some time. Proposed solutions range from the simple, like putting better locks on doors, to the experimental, like automatic face-recognition systems. On a long-term basis, they even include architectural measures: designing buildings so that bomb-laden trucks cannot readily approach them. The privacy aspects of such surveillance are discussed in this article